2010
DOI: 10.1016/j.habitatint.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of residential satisfaction in newly designed public low-cost housing in Kuala Lumpur, Malaysia

Abstract: a b s t r a c tThis paper provides an assessment of residential satisfaction of newly designed public low-cost housing dwellers of Kuala Lumpur, Malaysia, with forty-five variables grouped into five components -dwelling unit features, dwelling unit support services, public facilities, social environment and neighbourhood facilities. Findings from the study indicate that the residents are moderately satisfied with dwelling unit support services, followed by public and neighbourhood facilities than dwelling unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
320
9
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(435 citation statements)
references
References 23 publications
32
320
9
4
Order By: Relevance
“…Therefore, benefits can be maximized if HQ and satisfaction are improved at the planning and design stages by incorporating participation strategies and considering homebuyers' HQ opinions. The result is consistent with some studies that revealed that housing providers should regulate their housing activities and design accuracy at the original design stage in order to suit households' needs and wants by examining factors that account for housing satisfaction or dissatisfaction [2][3][4]. …”
Section: Cost Performance Of Homebuyers' Quality Improvement Strategiessupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, benefits can be maximized if HQ and satisfaction are improved at the planning and design stages by incorporating participation strategies and considering homebuyers' HQ opinions. The result is consistent with some studies that revealed that housing providers should regulate their housing activities and design accuracy at the original design stage in order to suit households' needs and wants by examining factors that account for housing satisfaction or dissatisfaction [2][3][4]. …”
Section: Cost Performance Of Homebuyers' Quality Improvement Strategiessupporting
confidence: 88%
“…Quality positioning and facilities planning are confirmed once the construction project is complete, leaving little room for improving quality items. A number of studies have indicated that project quality and contractor satisfaction can be greatly enhanced if HQ can be improved during the planning stage of a construction project [2,23]. The presale housing system is a popular system in Asia.…”
Section: Cost-orientated Housing Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This, along some other scarce international articles has indicated that the study of the topic is still elusive but universal. It is prudent that local context scenario is sufficiently addressed, as in a study conducted by (Mohit, Ibrahim, & Rashid, 2010) with the satisfaction of residents in public low-cost housing in Kuala Lumpur. In that particular study, forty-five variables have been identified and clustered into components.…”
Section: The Neighbourhood Unitmentioning
confidence: 99%
“…Early literature of these discussions includes Jane Jacobs"s, "Life and Death of Great American Cities" in 1961 and Mayo"s, "Effects of Street Forms on Suburban Neighboring Behavior" in 1979. The studies of Mohit, Ibrahim & Rashid (2010), Zakaria and Yang (2004), Nurizan (1993) are among the few Malaysian researchers examining neighbourhoods (lowcost housing) and quality of life. Such academic debates are rather limited in Malaysian literature of the built environment.…”
mentioning
confidence: 99%